Peran Nadzir Dalam Mengelola Harta Benda Wakaf Untuk Meningkatkan Kesejahteraan Umat - Shaifudin, Rafi Nur; Fahrullah, (Universitas Negeri Surabaya, 2022)
Waqf management can be a solution in improving community welfare. Management with a good nadzir role will bring benefits to the community. Baiturrahmah Foundation is one of the foundations that has a waqf management program. This research was conducted in order to see the improvement of welfare through waqf management through the role of nadzir. The research method is qualitative which has the result that there is an increase in welfare in the field of education in the community. However, Nadzir at the Baiturrahmah Foundation is still learning a lot and is not yet professional because in terms of SDI (Human Resources) it is still common and it is necessary to increase the scale of knowledge in terms of waqf and Nadzir operations properly. Nadzir standardization needs to be carried out in supporting professionals in managing cash waqf assets or assets by attending a nadzdiran school which will later be fostered and given training related to nadzir in accordance with Islamic law and will get a nadzir certification which will later be implemented in a good management way in an institution.